1997
DOI: 10.1159/000112896
|View full text |Cite
|
Sign up to set email alerts
|

The Besangon Stroke Registry: An Acute Stroke Registry of 2,500 Consecutive Patients

Abstract: The purpose of this study was to estimate the frequency of various risk factors, courses and outcome of stroke subtypes in a large hospital-based stroke registry. The Centre Hospitalier Universitaire of Besançon is the only public hospital with a neurological department in the county to admit any unselected patient with an acute stroke. A prospective hospital-based registry using systematic computer coding of data was conducted. All patients were evaluated by standard testing (neuroimaging, Doppler ultrasonogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
97
3
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(116 citation statements)
references
References 0 publications
13
97
3
2
Order By: Relevance
“…On the other hand, the low rate of diabetes in Senegalese may be due to their Sahelien style of life and the possible existence of environmental factors which may influence the risk of diabetes cannot be totally excluded. The prevalence rate of diabetes in stroke patients is similar to ours in Europe [15] but lower than 45% reported in Saudi Arabia [14]. We found regular consumption of alcohol to be an important vascular risk factor in this study, present in 28.30% of cases.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…On the other hand, the low rate of diabetes in Senegalese may be due to their Sahelien style of life and the possible existence of environmental factors which may influence the risk of diabetes cannot be totally excluded. The prevalence rate of diabetes in stroke patients is similar to ours in Europe [15] but lower than 45% reported in Saudi Arabia [14]. We found regular consumption of alcohol to be an important vascular risk factor in this study, present in 28.30% of cases.…”
Section: Discussionsupporting
confidence: 85%
“…Sagui et al in Dakar, Senegal found a mean age of 61.9 ± 12.4 in 2008 in Dakar [12], a result similar to that of other developing countries [13] [14]. The mean age in the current study is 8 to 15 years lower than that observed in developed countries [15] [16]. Situation is same with life expectancy between developing and developed countries.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Many studies have shown higher mean admission glucose level in nonsurvivors of stroke compared with survivors [32][33][34]. Furthermore, two large studies demonstrated that glucose level at hospital admission was a significant predictor of mortality [35] or poor functional recovery [36] after stroke independent of other prognostic factors. In addition, a study showed that persistent hyperglycemia was an independent determinant of infarct expansion and was associated with worse functional outcome [37].…”
Section: Discussionmentioning
confidence: 99%